The covid 19 pandemic and its impact on higher education - Diaz Lazo, Anibal (2020)
The world is experiencing the coronavirus disease pandemic (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which started in Wuhan (China) at the end of December 2019; progressively spreading worldwide and currently affecting more than two hundred countries (Zhang, 2019; WHO, 2020). In Latin America, the highest incidence rates per 100 000 inhabitants correspond to Chile with 1200 cases and Peru with 730.6 cases (WHO, 2020).